Unusual odontogenic keratocyst with impacted maxillary central incisor: A diagnosis challenge - Purnamasari, Shinta; Marks, Luc A. M.; Devi Oktaviani, Paramita; Merlynike Leo, Leviena; Mulyawan, Indra; Rahayu, Retno Pudji; Saskianti, Tania (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2024)
Background: Odontogenic keratocyst (OKC) is considered an odontogenic cyst, with the unique clinical characteristics of this entity being local destruction, aggressive behavior, a high recurrence rate, specific histopathologic features, and the tendency for multiple lesions when associated with syndromes. Odontogenic keratocyst accounts for 12–14% of all cysts in the jaws. Purpose: The aim of this case report is to present an unusual odontogenic keratocyst associated with impacted maxillary central incisor, case management of anterior maxilla odontogenic keratocyst involving an adjacent tooth, and its postoperative six-month follow-up. Case: A 13-year-old female patient was referred to the Universitas Airlangga Hospital with a complaint that her upper front teeth had not erupted. The parents revealed that the patient had suffered trauma from falling down the stairs at the age of four, i.e., eight years ago. Case Management: The cyst was enucleated together with the associated permanent upper right central incisor, retained deciduous upper right central incisor, the permanent upper right lateral incisor, and upper right canine. Post surgical treatment, the patient used a partial denture to increase her self-confidence. Conclusion: Enucleation of the cyst with extraction of the permanent teeth should be performed to avoid recurrence of the OKC. Periodic radiographic evaluation is required with long-term follow-up.